Ang pagmina dinhi sa Loreto a documentary photography - Laid, Jonathan R.
This research focused on Documentary photography and the mining processes involved in the municipality of Loreto, Province of Dinagat Island. This study aimed to express responsible mining in the Philippines through Documentary Photography. It also aims to answer the question ?How will the photos be composed that target human emotion and tell its target audiences or the general public the situation about mining? The research aimed to present with a documentary photography on mining process as the end product of this production-led research. The photographs will highlight the following content: the photograph itself and the corresponding cutline for each photograph about the real and current situation of mining in the Philippines. The images play a vital role in the documentary photography as they served as the main focus. Thus, this study highlights photography specifically documentary photography as the channel to tell the messages. The image were carefully selected to effectively tell the message, and by the image alone, audience will be able to at least create a hint and grasp what the message could be